(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2024)
This article shares the experience generated by an extension project in border towns of Costa Rica, which is an alliance between the local government of the Canton of Upala and the public university. The objective of this project is to reduce the technological gap in the districts of Las Delicias, Central and San José de Upala through robotics, programming and creative reading using the theme of sustainable cities as a transversal axis. A strategy based on the STEAM approach is implemented, which promotes interdisciplinary learning through practical workshops and didactic guides. During the implementation of the project, significant achievements were made, such as the participation of students and the transfer of knowledge on sustainable cities and robotics. Teachers and librarians were trained to replicate the workshops autonomously, ensuring the long-term sustainability of the project.